Qualidade fisiológica e sanitária de sementes de Cordia americana (L.) Gottschling & J. S. Mill - Walker, Clair (2013)
Cordia americana (L.) Gottschling & J.S.Mill. (guajuvira) is a forest species widely distributed in Brazil with importance in its economics and environment. Therefore, there is a great demand of research in seed technology for this species, as for the physiological and sanitary quality of seeds and, mainly, for the association of Fusarium spp. The objectives of this study were to determine the physiological maturity and seed collecting system to be more favorable to sanitary and physiological quality of the C. americana seeds and evaluate the pathogenicity of Fusarium sp. associated with them, morphological and molecularly characterizing the pathogen on the species level. The phenology of this species was closely observed during the development stages and, after the maturation onset of its fruits, they were collected in the plant and its soil. After the picking, it was determined the moisture content of the seeds, the period of maximum dry weight mass accumulation, maximum germination and vigor, besides, sanitary quality ratings. Through the transmission tests, it was found to occur Fusarium spp. causing disease symptoms in seedlings. After obtaining four isolates of the fungus, they were inoculated in seeds to prove its pathogenicity. The morphological characterization was performed using an identification key for the genus Fusarium and, for the molecular identification, genomic regions ITS were sequenced with its elongation factor 1-α. The results may conclude that physiological maturation in C. americana seeds occurs at 52 days after anthesis and the species F. acuminatum and F. verticillioides were pathogenic to species, causing damping-off in pre and post emergence.